Political epistemics : the secret police, the opposition, and the end of East German socialism - Glaeser, Andreas (Chicago studies in practices of meaning., 2011)
What does the durability of political institutions have to do with how actors form knowledge about them? Andreas Glaeser investigates this question in the context of a fascinating historical case: socialist East Germanys unexpected self-dissolution in 1989. His analysis builds on extensive in-depth interviews with former secret police officers and the dissidents they tried to control as well as research into the documents both groups produced. In particular, Glaeser analyzes how these two opposing factions understanding of the socialist project came to change in response to countless everyday experiences. These investigations culminate in answers to two questions: why did the officers not defend socialism by force? And how was the formation of dissident understandings possible in a state that monopolized mass communication and group formation? He also explores why the Stasi, although always well informed about dissident activities, never developed a realistic understanding of the phenomenon of dissidence. Out of this ambitious study, Glaeser extracts two distinct lines of thought. On the one hand he offers an epistemic account of socialisms failure that differs markedly from existing explanations. On the other hand he develops a theorya sociology of understandingthat shows us how knowledge can appear validated while it is at the same time completely misleading.